A sensitive suspended sediment sensor for the detection of total suspended solids (TSS) - Lim, Hwee San; Mat Jafri, Mohd Zubir; Abdullah, Khiruddin; Daraigan, Sami Gumaan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
A novel optical sensor has been designed and developed to measure light through water samples for the retrieval of total suspended solids (TSS) concentrations. Light-emitting diodes (LED) were used as light sources of this sensor. In case 1, light was transmitted through the sample when the angle between light source and photodiode was 180°, and for case 2, light was scattered by small particles in the sample when the angle between light source and photodiode was 90°. An algorithm equation was developed and used to determine the relationship between measured TSS and predicted TSS.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 631-637
Keywords: optyka; light emitting diode (LED); total suspended solids (TSS)